Biodiversity of underutilized food plants in a community-based learning garden - Michelle Medeiros Jacob (Universidade do Estado do Rio de Janeiro, 2020)
Underutilized food plants (UFP) offer the opportunity to overcome issues that are currently facing sustainable food systems. The scarcity of data on them and the gaps found in the nutrition workforce are challenges that limit their approach. To addresses some of them, a community-based garden project was developed in an undergraduate program in nutrition at a federal university in northeastern Brazil. This paper aims to present the results obtained with this project in its first twelve months concerning the use of Garden-Based Learning (GBL). During 2018 eight plants were studied with the support of this method. The data gathered on UFP by students included: botanical family, vernacular names, origin, the biome of occurrence, food uses, and nutritional indicators. The use of GBL involved some strategies such as definition of theme, elaboration of a culmination product, and fostering the research of different kinds of knowledge. The GBL method mediated the educational process implied with concepts, practices, and attitudes. The plants studied have the potential to contribute with Food and Nutrition Security due some criteria such as adequacy to the biome of the study setting and variety of nutrients. Recognize native and adapted food plants resilient to the dry landscape is central to enhance environmental and human health. The resulting data served as a basis to promote sustainable diets with the surrounding community, from lectures to hands-on activities in the garden and kitchen.